168k views
2 votes
Solve 8[7 - (6x - 6)] + 6x = 0.

User Orakull
by
6.5k points

2 Answers

2 votes
So first we need to solve whatever that is in the brackets.
Distribute the negative sign to both 6x and -6.
U will get 7 - 6x + 6 which equals to 13 - 6x.
Now we must distribute the 8 to both 13 and -6x.
This results in 104 - 48x.
Now u have 104 - 48x + 6x = 0
Combine -48x + 6x and subtract 104 on both sides.

-42x = -104
X = 52/21
User Zack Morris
by
7.4k points
3 votes
Its x = 52/21 = 2.47
User JGV
by
6.6k points